Open Observing Users to Gain Insight in Lanna Mural Paintings with Responsive Website for Education - Tawipas Pichaichanarong (Graduate School of Institut Seni Indonesia Yogyakarta, 2023)
One of the major effects of Covid-19 upon the entire world from December 2019 onwards were the severe restrictions placed upon global and domestic movements. Adhering to lockdown measures, most individuals around the world were unable to travel, either within their own country or abroad. However, during this unprecedented period, the researcher addressed the issue and devised an alternative opportunity for those wishing to visit the temple Wat Phumin in Nan province, Thailand based on previous research. The outcome was funded by the Office of Contemporary Art and Culture (OCAC), Thailand in 2017 to develop Lanna mural paintings and the narratives they depicted into moving images, with the focus on the tales of the Jataka (a body of literature relating to the Buddha’s previous lives). In addition to using the findings of previous research in this study, the researcher designed for use the images of Lanna mural paintings and the moving images of the Jataka tales of Khatthana Kumara Jataka and Nimi Jataka in cooperation with responsive websites to gain a better understanding of Lanna mural paintings at Wat Phumin in Nan province through different platforms. In addition, in the context of distance education design, the use of responsive websites to facilitate the exploration and understanding of Lanna mural paintings at Wat Phumin presents a unique and innovative approach. For methodology, open observation and qualitative study were used by interviewing selected participants.This research study has determined that responsive websites are an effective alternative tool for individuals worldwide to explore and deepen their understanding of Lanna mural paintings at Wat Phumin in Nan province. The accessibility of these websites has become especially valuable during a period of limited travel and restricted mobility experienced in recent years. By utilizing responsive websites, visitors can now gain valuable insights into the rich artistic heritage of Lanna mural paintings, transcending physical limitations and geographical boundaries. This educational resource opens up new avenues for cultural exploration and promotes global appreciation of Wat Phumin's remarkable artistic treasures.Pengguna Observasi Terbuka untuk Menambah Wawasan Lukisan Mural Lanna dengan Web Responsif untuk Edukasi Abstrak Salah satu dampak besar Covid-19 terhadap seluruh dunia mulai bulan Desember 2019 dan seterusnya adalah pembatasan ketat terhadap pergerakan global dan domestik. Karena penerapan lockdown, sebagian besar orang di seluruh dunia tidak dapat melakukan perjalanan, baik di dalam negeri maupun ke luar negeri. Namun, selama periode yang belum pernah terjadi sebelumnya ini, peneliti mengatasi masalah tersebut dan merancang peluang alternatif bagi mereka yang ingin mengunjungi kuil Wat Phumin di provinsi Nan, Thailand berdasarkan penelitian sebelumnya. Hasil penelitian ini didanai oleh Kantor Seni dan Budaya Kontemporer (OCAC), Thailand pada tahun 2017 untuk mengembangkan lukisan mural Lanna dan narasi yang digambarkannya ke dalam gambar bergerak, dengan fokus pada kisah Jataka (kumpulan literatur yang berkaitan dengan kehidupan Buddha sebelumnya). Selain menggunakan temuan penelitian sebelumnya dalam penelitian ini, peneliti merancang untuk menggunakan gambar lukisan mural Lanna dan gambar bergerak kisah Jataka Khatthana Kumara Jataka dan Nimi Jataka bekerja sama dengan website responsif untuk mendapatkan pemahaman yang lebih baik tentang Lukisan mural Lanna di Wat Phumin di provinsi Nan melalui berbagai platform. Selain itu, dalam konteks perancangan pendidikan jarak jauh, pemanfaatan website responsif untuk memudahkan eksplorasi dan pemahaman lukisan mural Lanna di Wat Phumin menghadirkan pendekatan yang unik dan inovatif. Untuk metodologi, observasi terbuka dan studi kualitatif digunakan dengan mewawancarai partisipan terpilih. Studi penelitian ini menentukan bahwa situs web responsif adalah alat alternatif yang efektif bagi individu di seluruh dunia untuk mengeksplorasi dan memperdalam pemahaman mereka tentang lukisan mural Lanna di Wat Phumin di provinsi Nan. Aksesibilitas situs web ini menjadi sangat berharga selama periode terbatasnya perjalanan dan terbatasnya mobilitas yang dialami dalam beberapa tahun terakhir. Dengan memanfaatkan situs web responsif, pengunjung kini dapat memperoleh wawasan berharga tentang kekayaan warisan seni lukisan mural Lanna, yang melampaui keterbatasan fisik dan batas geografis. Sumber daya pendidikan ini membuka jalan baru untuk eksplorasi budaya dan mempromosikan apresiasi global terhadap kekayaan seni Wat Phumin yang luar biasa.